ASSESSMENT OF THE СURRENT STATE AND SUSTAINABILITY PROSPECTS OF POPULUS × CANESCENS (AITON) SM. POPULATIONS IN THE MIDDLE REACHES OF THE URAL RIVER WEST KAZAKHSTAN REGION (Experimental biology, 2026)
This study presents the results of a comprehensive botanical and biogeographical investigation of Populus × canescens (Aiton) Sm. populations within the middle reaches of the Ural River in the West Kazakhstan region. The assessment integrates field surveys, herbarium data, and floristic analyses to evaluate the current condition, structural organization, and ecological resilience of grey poplar communities.A total of eight distinct populations were identified, primarily associated with floodplain and near - terrace habitats of the Ural River valley. Floristic analysis documented 103 vascular plant species from 37 families and 83 genera. The biomorphological structure of the flora is dominated by perennial herbaceous polycarpic species 64%, along with a substantial representation of woody and shrubby taxa 22.3%.Phytocenotic evaluation revealed six major ecological - coenotic groups - forest, meadow, steppe, forest - steppe, meadow-marsh, and riparian - aquatic - with forest 31% and meadow 25.2% elements prevailing.
Keywords: Populus × canescens, floodplain ecosystems, grey poplar communities, biomorphology, chorology, Ural River, West Kazakhstan.